The use of taping in the postoperative period of plastic surgery (Research, Society and Development, 2021)
Conceptualizes that aesthetic plastic surgery (CPE) seeks to remodel normal parts of the body for beauty and self-esteem. For having presented excellent results and for the positive personal observation of the professional in the evolution of the postoperative period, the athletic tape has been increasingly requested by the plastic surgery team. The objective of this work is to present the results presented by the use of taping in the postoperative period of plastic surgery, as well as the benefits of its various applicability to alleviate manifestations of surgery. It is a narrative literature review, seeking an update and a means of obtaining information on a given topic in a short period of time. The search was carried out in the following databases: Scientific Electronic Library Online (sciELO), Google Scholar, PUBMED and LILACS (Latin American and Caribbean Health Sciences) as well as in books related to the proposed theme. Therefore, articles deal with the use of elastic bandage as a physical therapy resource in the postoperative period of plastic surgery, with common goals such as preventing and treating edema, ecchymosis, fibrosis and scarring changes resulting from the surgery. Finally, although the bandages are stimulating the recovery of patients after plastic surgery and the results seem to be more and more promising, it is a fact that, as this is a new technique, there is a lack of scientific studies that prove the therapeutic effect caused by the elastic bandage during the postoperative period, as well as what question some bases of the technique.